Facial deformations during nasal continuous positive airway pressure therapy. Issue 16 (8th December 2016) - Sims, Andrew; Simmons, Anne; Hoffman, Mark; Schindhelm, Klaus
Abstract: Obstructive Sleep Apnoea (OSA), characterised by repeated collapse of the pharyngeal airway during sleep, causes cessation of breathing followed by arousal, restoring normality. Continuous Positive Airway Pressure (CPAP) is a non-invasive, effective treatment for OSA where positive pressure is applied to the airway through a mask, maintaining patency. Nasal masks are commonly used, contacting the face across the upper lip, sides of the nose and the nasal bridge. Despite health benefits, therapy compliance is sub-optimal, often due to poor mask fit and discomfort. Masks have been designed to conform to the facial profile, but have not taken into account facial deformations. The nature of facial deformations while undergoing CPAP therapy is unknown. This study investigates the facial deformations experienced by a patient while undergoing nasal CPAP therapy. Magnetic Resonance Imaging (MRI) scans of the face were acquired of participants in the reference configuration and while undergoing CPAP therapy. The CPAP scan volume was registered onto the reference volume prior to surface generation for each state. Perpendicular deformation was measured from the reference facial profile to the deformed profile. Large facial deformations were measured at the sides of the nose ( 4.6 ± 1.6 mm ) and the upper lip ( 4.9 ± 1.8 mm ) with much smaller deformations at the nasal bridge ( 2.4 ± 0.2 mm ) . When normalised by applied load and tissue thickness, no difference was found. These findings and techniques can be used to consider facial deformation in the development of future nasal CPAP masks to improve comfort and compliance to therapy.